Stain-resistant, anti-skid and wear-resistant composite layer, ceramic tile and preparation method and application thereof

By forming a wear-resistant anti-slip layer and corundum layer on the surface of the tiles, combined with a hydrophobic and stain-resistant coating, the existing anti-slip tiles have been solved, and high-level anti-slip performance and easy-to-cleanness are achieved.

CN119569482APending Publication Date: 2025-03-07FOSHAN DONGPENG CERAMIC +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411781881.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The surface of existing anti-slip tiles is rough after being fired at high temperature, which is prone to concealing dirt and unstable anti-slip performance. The anti-slip properties decrease after long-term use, affecting public safety.

Method used

Matt dry particles with an initial melting temperature of 1200℃ or above are used to form a wear-resistant and antique protective glaze, and corundum layer is formed with corundum slurry, combined with a hydrophobic and stain-resistant coating to form a rough composite structural surface at the micron level and nano level.

Benefits of technology

It has achieved anti-slip of ceramic products above R11, and has the characteristics of hydrophobic and easy cleaning, solving the problem that existing ceramic surfaces cannot be both stain resistance, anti-slip and Mohs hardness.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a stain-resistant, anti-skid and wear-resistant composite layer, a ceramic tile and a preparation method and application thereof. The stain-resistant, anti-skid and wear-resistant composite layer sequentially comprises a wear-resistant and anti-skid layer and a corundum layer from the bottom surface to the top surface, the wear-resistant anti-slip layer is prepared from anti-slip dry granular glaze; the non-slip dry granular glaze is prepared from the following raw materials: antique protection glaze and matte dry granules, the antique protection glaze is subjected to ball milling until the screen residue of 325 meshes is 0.2-1.5%, and the content of BaO and MgO is greater than 20%; the granularity range of the matte dry granules is 120-300 meshes, and the initial melting temperature is higher than 1200 DEG C; the corundum layer is prepared from corundum slurry; the corundum slurry comprises the following raw materials: corundum powder and a suspending agent. According to the scheme, the wear-resistant anti-skid layer is matched with the corundum layer to form a micron-scale and nano-scale rough composite structure surface, the wear-resistant anti-skid layer can be combined with a hydrophobic and stain-resistant coating to enable the surface skid resistance of a ceramic product to reach R11 or above, the ceramic product is hydrophobic and easy to clean, and the problem that the stain resistance, the skid resistance and the Mohs hardness of existing ceramic cannot be combined at the same time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic tiles, and in particular to a stain-resistant, non-slip, and wear-resistant composite layer, ceramic tiles, and a preparation method and application thereof. Background Art

[0002] The existing anti-slip tile preparation process requires the use of dry granular materials with coarse particles and high temperature so that the anti-slip level of the prepared glaze meets the requirements. The main thing is to retain the rough surface after high-temperature firing in the kiln. The product's anti-slip level reaches R11 or above to have a significant anti-slip effect. However, there are often some tiny gaps between the dry particles with rough surfaces, which can easily lead to surface conditions such as dust accumulation, dirt accumulation, and difficulty in cleaning; at the same time, if the dry particle temperature is reduced and ultra-fine dry particles are used, the anti-slip performance index of the brick surface will decrease, and the anti-slip level cannot be stabilized above R11; further, anti-slip tiles are generally used in outdoor public places with large traffic, which means that the soles of shoes and the sand on the soles of shoes rub against the surface of the anti-slip tiles for a long time, causing the raised anti-slip dry particles on the surface of the anti-slip tiles to be easily worn, resulting in a decrease in anti-slip performance after long-term use, affecting public safety. Summary of the invention

[0003] The purpose of the present invention is to propose a stain-resistant, anti-skid and wear-resistant composite layer, which selects matte dry particles with an initial melting temperature of more than 1200°C and antique protective glaze to form a wear-resistant and anti-skid layer, and uses corundum slurry to form a corundum layer. The combination of the wear-resistant and anti-skid layer and the corundum layer can form a rough composite structure surface at the micron level and nanometer level, which can be combined with a hydrophobic and stain-resistant coating to make the surface of the ceramic product anti-skid reach R11 or above, and the surface also has the characteristics of being hydrophobic and easy to clean.

[0004] The present invention also provides a stain-resistant, non-slip and wear-resistant ceramic tile, which is provided with the stain-resistant, non-slip and wear-resistant composite layer mentioned above.

[0005] The present invention also provides a method for preparing a stain-resistant, anti-skid, and wear-resistant composite layer, which is used to prepare the stain-resistant, anti-skid, and wear-resistant composite layer.

[0006] The invention also proposes a use of the composite layer in preparing stain-resistant, non-slip and wear-resistant ceramic tiles.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A stain-resistant, skid-resistant, and wear-resistant composite layer, comprising, from the bottom surface to the top surface, a wear-resistant and skid-resistant layer and a corundum layer;

[0009] The wear-resistant and anti-skid layer is made of anti-skid dry granular glaze; the raw materials of the anti-skid dry granular glaze include, by mass percentage: 10-80% of antique protective glaze and 20-90% of matte dry granules;

[0010] The antique protective glaze is ball-milled to a 325-mesh sieve residue of 0.2-1.5%, and the content of BaO plus MgO is greater than 20%; the particle size range of the matte dry particles is 120-300 mesh, and the initial melting temperature is greater than 1200°C;

[0011] The corundum layer is made of corundum slurry; the raw materials of the corundum slurry include, by mass percentage: 10-60% corundum powder and 40-90% suspending agent;

[0012] The particle size of the corundum powder ranges from 200 to 1200 meshes.

[0013] It can be optimized to further include: a hydrophobic and anti-fouling coating;

[0014] The hydrophobic and anti-fouling coating is applied on the surface of the corundum layer;

[0015] The hydrophobic and anti-fouling coating is made of a hydrophobic and anti-fouling paint, and the hydrophobic and anti-fouling paint comprises: hydrogenated silicone oil, organic silicone resin, nano silicon dioxide, a silane coupling agent and a polysilazane resin.

[0016] Optimally, the antique protective glaze comprises, by mass, 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 6 to 10 parts of kaolin, 2 to 8 parts of zinc oxide, 3 to 10 parts of burned talc, 5 to 15 parts of wollastonite, 15 to 25 parts of barium carbonate and 2 to 8 parts of strontium carbonate.

[0017] Optimally, the matte dry particles include, by mass percentage, SiO2 45-65%, Al2O3 6-15%, K2O 3-10%, Na2O 0-2.5%, CaO 6-15%, MgO 0-1%, BaO 0-2% and ZnO 3-12%.

[0018] A stain-resistant, non-slip and wear-resistant ceramic tile, comprising: a body and the stain-resistant, non-slip and wear-resistant composite layer;

[0019] The anti-fouling, anti-skid and wear-resistant composite layer is arranged on the surface of the blank.

[0020] A method for preparing a stain-resistant, anti-skid, and wear-resistant composite layer, which is used to prepare the stain-resistant, anti-skid, and wear-resistant composite layer, comprises the following steps:

[0021] (1) applying anti-skid dry granular glaze cloth to the surface of the substrate to form a wear-resistant and anti-skid layer;

[0022] (2) applying corundum slurry to the wear-resistant and anti-skid layer to form a corundum layer;

[0023] (3) The substrate is transferred to a kiln and fired at 1200-1300°C.

[0024] It can be optimized that in step (1), the glazing parameters of the anti-slip dry granular glaze are: specific gravity 1.2-1.6 g / cm 3 , glaze spraying amount 100 ~ 250g / square meter, nozzle aperture 0.43 ~ 0.72mm;

[0025] In the step (2), the glazing parameters of the corundum slurry are: specific gravity 1.05-1.4 g / cm 3 The glaze spraying amount is 50-200g / square meter, and the nozzle aperture is 0.36-0.52mm.

[0026] Optionally, the method further comprises: step (4);

[0027] Step (4): After the substrate is taken out of the kiln, it is cooled to 100-250° C., a hydrophobic and anti-fouling coating is applied to the surface of the substrate, and the hydrophobic and anti-fouling coating is cured by the residual heat of the substrate itself;

[0028] The hydrophobic and anti-fouling coating includes: hydrogenated silicone oil, polysilazane resin, nano-silica and silane coupling agent.

[0029] Preferably, in step (4), the hydrophobic and anti-fouling coating is applied by spraying.

[0030] A use of a composite layer in preparing stain-resistant, non-slip and wear-resistant ceramic tiles, wherein the composite layer is the above-mentioned stain-resistant, non-slip and wear-resistant composite layer, or is prepared by the above-mentioned method for preparing the stain-resistant, non-slip and wear-resistant composite layer.

[0031] Compared with the prior art, one of the above technical solutions has the following beneficial effects:

[0032] The present invention provides a stain-resistant, non-slip and wear-resistant composite layer, which uses matte dry particles with an initial melting temperature of more than 1200°C and antique protective glaze to form a wear-resistant and non-slip layer, and uses corundum slurry to form a corundum layer. The combination of the wear-resistant and non-slip layer and the corundum layer can form a rough composite structure surface at the micron level and the nanometer level, which can be combined with a hydrophobic and stain-resistant coating to make the surface of the ceramic product anti-slip reach R11 or above, and the surface also has the characteristics of being hydrophobic and easy to clean, which solves the problem that the existing ceramic surface cannot have stain resistance, anti-slip properties and Mohs hardness at the same time. DETAILED DESCRIPTION

[0033] For ease of understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the documents in this area or the product instructions are carried out. The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be obtained by commercial purchase.

[0034] A stain-resistant, skid-resistant, and wear-resistant composite layer, comprising, from the bottom surface to the top surface, a wear-resistant and skid-resistant layer and a corundum layer;

[0035] The wear-resistant and anti-skid layer is made of anti-skid dry granular glaze; the raw materials of the anti-skid dry granular glaze include, by mass percentage: 10-80% of antique protective glaze and 20-90% of matte dry granules;

[0036] The antique protective glaze is ball-milled to a 325-mesh sieve residue of 0.2-1.5%, and the content of BaO plus MgO is greater than 20%; the particle size range of the matte dry particles is 120-300 mesh, and the initial melting temperature is greater than 1200°C;

[0037] The corundum layer is made of corundum slurry; the raw materials of the corundum slurry include, by mass percentage: 10-60% corundum powder and 40-90% suspending agent;

[0038] The particle size of the corundum powder ranges from 200 to 1200 meshes.

[0039] The present invention provides a stain-resistant, non-slip and wear-resistant composite layer, which uses matte dry particles with an initial melting temperature of more than 1200°C and antique protective glaze to form a wear-resistant and non-slip layer, and uses corundum slurry to form a corundum layer. The combination of the wear-resistant and non-slip layer and the corundum layer can form a rough composite structure surface at the micron level and the nanometer level, which can be combined with a hydrophobic and stain-resistant coating to make the surface of the ceramic product anti-slip reach R11 or above, and the surface also has the characteristics of being hydrophobic and easy to clean, which solves the problem that the existing ceramic surface cannot have stain resistance, anti-slip properties and Mohs hardness at the same time.

[0040] Specifically, the antique protective glaze of this scheme can be replaced by the known antique protective glaze, which can be purchased directly from the market. Generally, antique protective glazes are mostly based on crystallization produced by high-barium formula or high-magnesium formula, while this scheme requires that the content of BaO plus MgO in the antique protective glaze is greater than 20%, and the known antique protective glaze can be fired at a temperature greater than 1200°C in a kiln. As the main component glaze, it is very suitable as a carrier of matte dry particles. In this way, it can be ensured that the matte dry particles maintain a certain "standing" state after firing, meeting certain initial anti-skid requirements; when the anti-skid dry particle glaze is applied to the substrate, as the liquid phase evaporates, the particles in the liquid phase begin to expose the surface, wherein the particles form a three-dimensional structure with a roughness range of 50 to 125 microns in the 120-300 mesh matte dry particles, which is a wear-resistant and anti-skid layer. As for the corundum slurry, after spraying, the surface of the substrate is covered with a thin layer of corundum particles, and the particle size of the corundum powder is 200-1200 meshes, which is arranged on the basis of the wear-resistant and anti-skid layer formed previously; because the matte dry particles and corundum are very resistant to high temperatures, the basic surface morphology before firing is still maintained after kiln firing, that is, the basic undulating surface with a roughness size in the range of microns and millimeters. Such a surface lays the foundation for anti-skid to reach R11 or above, and also prepares a good implantation for the subsequent preparation of hydrophobic and anti-fouling coatings.

[0041] Among them, the suspending agent is a conventional component in ceramic glazes, which can be purchased randomly from the market directly and can be selected into different types according to needs. It is generally composed of water-soluble high-molecular-weight high-viscosity materials or bentonite, etc. The amount of suspending agent added is generally adjusted according to the amount of matte dry particles and corundum powder added. The more corundum powder, the more suspending agent is added to ensure that the matte dry particles and corundum powder will not settle during glazing.

[0042] It can be optimized to further include: a hydrophobic and anti-fouling coating;

[0043] The hydrophobic and anti-fouling coating is applied on the surface of the corundum layer;

[0044] The hydrophobic and anti-fouling coating is made of a hydrophobic and anti-fouling paint, and the hydrophobic and anti-fouling paint comprises: hydrogenated silicone oil, organic silicone resin, nano silicon dioxide, a silane coupling agent and a polysilazane resin.

[0045] Among them, the mass ratio of hydrogenated silicone oil: silicone resin: nano-silica: silane coupling agent: polysilazane resin is (1.0-2.5):(5-15):(1.0-2.0):(0.1-0.6):(5-10).

[0046] This scheme preferably applies hydrophobic and stain-resistant coating, because by spraying, the hydrophobic and stain-resistant coating can be instantly filled into every gap of the base undulating surface with a roughness size in the micron and millimeter range, forming a complete film layer with a thickness of 1 to 5 microns; and the coating liquid flows under the action of its own weight, the deeper the depression, the thicker the film layer, and the corresponding stain-resistant and hydrophobic effects are more obvious.

[0047] Optimally, the antique protective glaze comprises, by mass, 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 6 to 10 parts of kaolin, 2 to 8 parts of zinc oxide, 3 to 10 parts of burned talc, 5 to 15 parts of wollastonite, 15 to 25 parts of barium carbonate and 2 to 8 parts of strontium carbonate.

[0048] The antique protective glaze of this scheme can be replaced with an antique protective glaze on the market as needed. In the optimal embodiment, the antique protective glaze is composed of potassium feldspar, sodium feldspar, kaolin, zinc oxide, burned talc, wollastonite, barium carbonate and strontium carbonate, and is mixed according to the above ratio to obtain the optimal embodiment, which lays the foundation for anti-slip performance reaching R12.

[0049] Optimally, the matte dry particles include, by mass percentage, SiO2 45-65%, Al2O3 6-15%, K2O 3-10%, Na2O 0-2.5%, CaO 6-15%, MgO 0-1%, BaO 0-2% and ZnO 3-12%.

[0050] Matt dry particles can be replaced by known matte dry particle formulas. Generally, this solution uses matte dry particles with an initial melting temperature of more than 1200°C to ensure that they maintain a certain "standing" state after firing and meet certain anti-slip requirements. In the best embodiment, the matte dry particles, by mass percentage, include: SiO2 45-65%, Al2O3 6-15%, K2O 3-10%, Na2O 0-2.5%, CaO 6-15%, MgO 0-1%, BaO0-2% and ZnO 3-12%, which can achieve the optimal anti-slip property of R12 and the optimal Mohs hardness of 8.

[0051] A stain-resistant, non-slip and wear-resistant ceramic tile, comprising: a body and the stain-resistant, non-slip and wear-resistant composite layer;

[0052] The anti-fouling, anti-skid and wear-resistant composite layer is arranged on the surface of the blank.

[0053] A method for preparing a stain-resistant, anti-skid, and wear-resistant composite layer, which is used to prepare the stain-resistant, anti-skid, and wear-resistant composite layer, comprises the following steps:

[0054] (1) applying anti-skid dry granular glaze cloth to the surface of the substrate to form a wear-resistant and anti-skid layer;

[0055] (2) applying corundum slurry to the wear-resistant and anti-skid layer to form a corundum layer;

[0056] (3) The substrate is transferred to a kiln and fired at 1200-1300°C.

[0057] It can be optimized that in step (1), the glazing parameters of the anti-slip dry granular glaze are: specific gravity 1.2-1.6 g / cm 3 , glaze spraying amount 100 ~ 250g / square meter, nozzle aperture 0.43 ~ 0.72mm;

[0058] According to this glazing parameter, the anti-slip dry granular glaze is applied, and the atomized droplet size is 0.02-0.08mm, and the size can be increased to 0.10-0.50mm through multiple superpositions, forming a "peak" basic layout. As the water in the droplets evaporates, the large and small particles in the droplets begin to appear on the surface, among which the matte dry particles of 120-300 mesh form a "tree and shrub" structure with a roughness range of 50-125 microns.

[0059] In the step (2), the glazing parameters of the corundum slurry are: specific gravity 1.05-1.4 g / cm 3 The glaze spraying amount is 50-200g / square meter, and the nozzle aperture is 0.36-0.52mm.

[0060] According to this glazing parameter, the "trees and shrubs" structure is covered with a thin layer of corundum particles. The corundum powder with a particle size of 200-1200 mesh is laid out three times on the basis of the "peaks" and "trees and shrubs" formed previously. The corundum particles formed on the surface are 10-75 microns, which is similar to the formation of the "leaf" structure on the basis of the "trees and shrubs".

[0061] In this way, because both matte dry particles and corundum powder are very resistant to high temperatures, the basic surface morphology before firing is still maintained after kiln firing, that is, a basic undulating surface in the micron and millimeter range is formed. Such a surface lays the foundation for anti-slip to reach R12 or above, and also prepares a good implantation for the subsequent preparation of hydrophobic and anti-fouling coatings.

[0062] Optionally, the method further comprises: step (4);

[0063] Step (4): After the substrate is taken out of the kiln, it is cooled to 100-250° C., a hydrophobic and anti-fouling coating is applied to the surface of the substrate, and the hydrophobic and anti-fouling coating is cured by the residual heat of the substrate itself;

[0064] The hydrophobic and anti-fouling coating comprises: hydrogenated silicone oil, polysilazane resin, nano-silicon dioxide and silane coupling agent, wherein the mass ratio of hydrogenated silicone oil: silicone resin: nano-silicon dioxide: silane coupling agent: curing agent is (1.0-2.5): (5-15): (1.0-2.0): (0.1-0.6): (5-10).

[0065] The hydrophobic and stain-resistant coating of this scheme preferably uses hydrogenated silicone oil, polysilazane resin, nano-silicon dioxide and silane coupling agent in combination. This is because the hydrophobic and stain-resistant coating is applied at a temperature of 100-250°C for the brick embryo. Under the action of high temperature, the silane coupling agent first produces a cross-linking reaction and begins to solidify, ensuring that the hydrophobic and stain-resistant coating film is firmly combined with the rough three-dimensional basic structure in the micron and millimeter range, and finally superimposed to form a hydrophobic surface with a roughness of micron + nanometer size. And its surface nanostructure contains silicon-hydrogen bonds of hydrogenated silicone oil and nano-silicon dioxide, which creates the final appearance of a hydrophobic and easy-to-clean surface. It solves the problem that the existing ceramic surface cannot have both stain resistance, anti-slip properties and Mohs hardness at the same time.

[0066] Preferably, in step (4), the hydrophobic and anti-fouling coating is applied by spraying.

[0067] This solution preferably applies the hydrophobic and anti-fouling coating by spraying or inkjet printing. The main advantage is that the hydrophobic and anti-fouling coating can be instantly filled into each gap in the base undulating surface with a roughness size in the micrometer and millimeter range to form a complete film layer with a thickness of 1 to 5 microns. Because the hydrophobic and anti-fouling coating has a certain fluidity under the effect of its own weight, the deeper the depression, the thicker the film layer, and the more obvious the corresponding anti-fouling and hydrophobic effect, especially it is very suitable for the surface of the wear-resistant and anti-skid layer and the corundum layer, so that the tile has both stain resistance, anti-skid and Mohs hardness.

[0068] A use of a composite layer in preparing stain-resistant, non-slip and wear-resistant ceramic tiles, wherein the composite layer is a stain-resistant, non-slip and wear-resistant composite layer of any of the above embodiments, or is prepared by a preparation method of a stain-resistant, non-slip and wear-resistant composite layer of any of the above embodiments.

[0069] Performance Test:

[0070] Anti-slip property: Use the "DIN51130 Anti-slip Test for Floor Plates" to conduct an anti-slip test on the brick surface.

[0071] Stain resistance: Using the test method of GB / T3810.14-2016 "Test methods for tiles Part 14 Determination of stain resistance - Building materials standard", the stain resistance of the product glaze is tested with the green dye in light oil as the pollutant. A stain resistance level of 5 is qualified.

[0072] Mohs hardness: The brick surface is tested on Mohs hardness according to European standard EN15771:2010.

[0073] Embodiment A1:

[0074] A method for preparing a stain-resistant, non-slip, and wear-resistant composite layer, comprising:

[0075] (1) Spray the anti-slip dry granular glaze on the brick with the base glaze attached. The construction parameters are: specific gravity 1.4g / cm 3 , glaze spraying amount 200g / m2, nozzle aperture 0.6mm; base glaze is purchased randomly on the market;

[0076] The anti-slip dry granule glaze, by mass percentage, includes: 50% antique protective glaze and 50% matte dry granules;

[0077] Antique protective glaze, including, by mass: 25 parts of potassium feldspar, 20 parts of sodium feldspar, 8 parts of kaolin, 6 parts of zinc oxide, 6 parts of burned talc, 10 parts of wollastonite, 20 parts of barium carbonate and 6 parts of strontium carbonate;

[0078] The chemical composition of the matte dry granules, by mass percentage, includes: SiO2 60%, Al2O3 11%, K2O 7%, Na2O2%, CaO 9%, MgO 1%, BaO 1% and ZnO 9%;

[0079] The antique protective glaze is ball-milled to 1% residue on a 325-mesh sieve; the particle range of the matte dry particles is 120 to 300 mesh, and the initial melting temperature is 1200°C.

[0080] (2) Spray the corundum slurry on the surface of the brick; the glazing parameters of the corundum slurry are: specific gravity 1.25g / cm 3 , glaze spraying amount 150g / m2, nozzle aperture 0.52mm;

[0081] The raw materials of the corundum slurry include, by mass percentage, 50% of corundum powder and 50% of suspending agent; the particle size of the corundum powder ranges from 200 to 1200 meshes. The suspending agent is purchased randomly on the market.

[0082] (3) The substrate is transferred to a kiln at 1250°C for firing; the bricks are taken out of the kiln and cooled to 150°C.

[0083] Embodiment A2:

[0084] The basic steps of Example A2 are the same as those of Example A1, with the only difference being that the antique protective glaze of Example A2 is purchased directly from the market, and the chemical composition of its raw materials, by mass percentage, includes: SiO2 50%, Al2O3 10%, K2O 3%, Na2O 3%, CaO 6%, MgO 1%, SrO 2%, BaO 20% and ZnO 5%.

[0085] Comparative Example A1:

[0086] The basic steps of Comparative Example A1 are the same as those of Example A1, except that step (2) is not performed in Comparative Example A1.

[0087] Comparative Example A2:

[0088] The basic steps of Comparative Example A2 are the same as those of Example A1, except that step (1) is not performed in Comparative Example A2.

[0089] Comparative Example A3:

[0090] The basic steps of Comparative Example A3 are the same as those of Example A1, except that the anti-slip corundum dry particle glaze of Comparative Example A3 uses ordinary dry particles instead of the matte dry particles of Example A1. The raw materials of the ordinary dry particles, by mass percentage, include: 30% of albite, 10% of potassium feldspar, 15% of dolomite, 10% of zircon powder, 10% of calcite, 5% of barium carbonate, 6% of fluorite and 14% of quartz.

[0091] The performance of Example A and Comparative Example A was tested, and the results are shown in Table 1.

[0092] Table 1 - Performance tests of Example A and Comparative Example A

[0093] project Anti-slip Mohs hardness Example A1 R10 Level 7 Example A2 R9 Level 6 Comparative Example A1 R7 Level 5 Comparative Example A2 R7 Level 5 Comparative Example A3 R7 Level 5

[0094] illustrate:

[0095] 1. By comparing Example A1 with Example A2, it can be seen that Example A2 uses the antique protective glaze on the market, while Example A1 uses the antique protective glaze recorded in this scheme, which is composed of potassium feldspar, sodium feldspar, kaolin, zinc oxide, burned talc, wollastonite, barium carbonate and strontium carbonate. The anti-skid properties and Mohs hardness of Example A1 and Example A2 can meet the performance requirements. Among them, the anti-skid property of Example A1 is R10 and the Mohs hardness is 7, which is better than Example A2 in terms of anti-skid property and Mohs hardness. It shows that the use of the antique protective glaze on the market in this scheme can meet the basic performance requirements of the anti-skid dry granular glaze, and the use of the raw materials of Example A1 can make the anti-skid property and Mohs hardness have both, and maintain the best.

[0096] 2. By comparing Example A1 with Comparative Example A1, it can be seen that Comparative Example A1 does not carry out step (2), and step (2) is mainly to apply corundum slurry; and the corundum slurry will form a three-dimensional corundum layer on the basis of the wear-resistant and anti-skid layer when fired. Comparative Example A1 only has a wear-resistant and anti-skid layer, and Comparative Example A1 does not have a corundum layer, that is, the basic undulating surface of the corundum powder part is missing. The corundum powder is melted at a high temperature of more than 2000 degrees, and it is completely melted. It is completely "standing up" when fired in a kiln at about 1250 degrees, so that it can form protruding sharp corners and edges on the basis of the wear-resistant and anti-skid layer, which is the most fundamental structure for anti-skid. Therefore, Comparative Example A1 is lower than Example A1 in terms of anti-skid property and Mohs hardness. The anti-skid property of Comparative Example A1 is only R7, and the Mohs hardness is only level 5. Example A1 combines the wear-resistant and anti-skid layer with the corundum layer. The anti-skid property of Example A1 is R10, and the Mohs hardness is level 7.

[0097] 3. By comparing Example A1 with Comparative Example A2, it can be seen that Comparative Example A2 does not carry out step (1), and step (1) is mainly to apply anti-skid dry granular glaze; Comparative Example A2 does not apply anti-skid dry granular glaze, but directly applies corundum slurry; and the particle size range of the matte dry granules in this scheme is 120-300 mesh, and the initial melting temperature is greater than 1200°C; and the antique protection glaze selected in this scheme can be fired at a temperature greater than 1200°C in the kiln, and can form a three-dimensional dry granular structure, so that the subsequent corundum powder with a particle size of 200-1200 mesh is arranged on the basis of this wear-resistant and anti-skid layer. Therefore, in the basic layout of Comparative Example A2, there is only corundum powder, and there is no ordinary dry granules; this scheme requires the dry granules and corundum to cooperate with each other, and the most important thing is that after the kiln is fired, the basic surface morphology before firing can still be maintained, that is, the basic undulating surface with a roughness size in the range of micrometers and millimeters, and this undulating surface can lay the foundation for the subsequent anti-skid to reach R11 or above. Comparative Example A2 does not have a three-dimensional structure of dry particles, so the stain resistance is only R7 and the Mohs hardness is only 5. Example A1 combines the wear-resistant and anti-skid layer with the corundum layer, and the anti-skid property of Example A1 is R10 and the Mohs hardness is 7.

[0098] 4. By comparing Example A1 with Comparative Example A3, it can be seen that Comparative Example A3 does not add matte dry particles to the anti-slip corundum dry particle glaze, but uses ordinary dry particles instead of matte dry particles; the initial melting temperature of the matte dry particles in this solution is greater than 1200°C; the initial melting temperature of the ordinary dry particles in Comparative Example A3 is 1100°C; the antique protection glaze selected in this solution can be fired at a temperature greater than 1200°C in a kiln, so it is necessary to ensure that the matte dry particles have an initial melting temperature greater than 1200°C; while the ordinary dry particles in Comparative Example A3 have melted before 1200°C, so before the basic structure is formed, the ordinary dry particles have begun to melt, and thus the dry particle structure cannot be formed. Therefore, in Comparative Example A3, there is only corundum powder on the basic structure, and there is no ordinary dry particles; because this solution requires the dry particles and corundum to cooperate with each other, based on the three-dimensional structure of "peaks" and "trees and shrubs" in the micrometer and millimeter range, the anti-slip performance of Example A1 can reach R10. Comparative Example A3 does not have a three-dimensional structure of dry particles, so the stain resistance is only R7 and the Mohs hardness is only level 5.

[0099] Embodiment B1:

[0100] The bricks prepared in step (3) of Example A1 are sprayed with a hydrophobic and stain-resistant coating, and the hydrophobic and stain-resistant coating is cured by the residual heat of the bricks themselves; the bricks are left to stand for 7 hours.

[0101] The hydrophobic and anti-fouling coating comprises: hydrogenated silicone oil, silicone resin, nano silicon dioxide, silane coupling agent and polysilazane resin; the size range of the nano silicon dioxide is 30nm.

[0102] The mass ratio of hydrogenated silicone oil: silicone resin: nano-silica: silane coupling agent: polysilazane resin is 1.5:10:1.5:0.5:7.

[0103] Embodiment B2:

[0104] The basic steps of Example B2 are the same as those of Example B1, with the only difference being that in step (1) and step (2), the hydrophobic and anti-fouling coating is applied to the blank by brushing.

[0105] The performance of Example B1 and Example B2 was tested, and the results are shown in Table 2 below.

[0106] Table 2 - Performance Tests of Example B

[0107] project Surface stain resistance Anti-slip Mohs hardness Example B1 qualified R12 Level 8 Example B2 qualified R10 Level 7

[0108] illustrate:

[0109] By comparing Example B1 with Example B2, it can be seen that Example B2 does not use spraying for construction, but uses brushing for construction; this solution uses spraying as the construction method, and the construction parameters are: specific gravity 1.2-1.6 g / cm3 The spraying amount of glaze is 100-250g / m2, and the nozzle aperture is 0.43-0.72mm, which can ensure that the size of the atomized droplets on the brick surface is 0.02-0.08mm, and after multiple stacking, the size increases to 0.10-0.50mm, forming the most basic three-dimensional basic structure. As the water in the droplets evaporates, the large and small particles in the droplets begin to appear on the surface. It is this spraying parameter that ensures the basic undulating surface formed by particles in the micron and millimeter range. While Example B2 is carried out on a horizontal surface by brushing, the film layer formed is also relatively thick, and the more the raised parts are brushed, the more unfavorable the anti-skid and Mohs hardness performance; therefore, the hydrophobic and anti-fouling coating of Example B2 only provides a certain anti-fouling property, but its anti-skid and Mohs hardness are not much improved relative to Example A1; while Example B1 is to apply the hydrophobic and anti-fouling coating by spraying, which can instantly fill the hydrophobic and anti-fouling coating into each gap of the basic undulating surface with a roughness size in the range of micrometers and millimeters, forming a complete film layer with a thickness of 1 to 5 micrometers; and the coating liquid flows under the action of its own weight, the deeper the depression, the thicker the film layer, and the more obvious the corresponding anti-fouling and hydrophobic effect. Example B1 is more stable than Example B2 in terms of the three-dimensional basic structure, so the anti-skid and Mohs hardness of Example B1 are better than those of Example B2, and the anti-skid property of Example B1 is the best R12, and the Mohs hardness is the best level 8, which shows that the use of spraying as the construction method of the hydrophobic and anti-fouling coating of this scheme can improve the anti-skid and Mohs hardness.

[0110] Example C:

[0111] A method for preparing a stain-resistant, non-slip, and wear-resistant composite layer, comprising:

[0112] (1) Spray the anti-slip dry granular glaze on the brick with the base glaze attached. The construction parameters are: specific gravity 1.2g / cm 3 , glaze spraying amount 250g / m2, nozzle aperture 0.72mm; base glaze was purchased randomly on the market;

[0113] The anti-slip dry granule glaze, by mass percentage, includes: 80% antique protection glaze and 20% matte dry granules;

[0114] Antique protective glaze, including, by mass: 30 parts of potassium feldspar, 15 parts of sodium feldspar, 6 parts of kaolin, 2 parts of zinc oxide, 10 parts of burned talc, 5 parts of wollastonite, 15 parts of barium carbonate and 2 parts of strontium carbonate;

[0115] The chemical composition of the matte dry granules, by mass percentage, includes: SiO2 50%, Al2O3 15%, K2O 10%, Na2O2.5%, CaO 11%, MgO 0.5%, BaO 2% and ZnO 9%;

[0116] The antique protective glaze is ball-milled to a 325-mesh sieve residue of 1.5%; the particle range of the matte dry particles is 120-200 mesh, and the initial melting temperature is 1200℃.

[0117] (2) Spray the corundum slurry on the surface of the brick; the glazing parameters of the corundum slurry are: specific gravity 1.05g / cm 3 , glaze spraying amount 200g / m2, nozzle aperture 0.36mm;

[0118] The raw materials of the corundum slurry include, by mass percentage, 60% of corundum powder and 4% of suspending agent; the particle size of the corundum powder ranges from 200 to 1200 meshes. The suspending agent is purchased randomly on the market.

[0119] (3) The substrate is transferred to a kiln at 1200°C for firing; the bricks are taken out of the kiln and cooled to 150°C; a hydrophobic and stain-resistant coating is sprayed on the bricks, and the hydrophobic and stain-resistant coating is cured by the residual heat of the bricks themselves; and the bricks are left to stand for 7 hours.

[0120] The hydrophobic and anti-fouling coating comprises: hydrogenated silicone oil, silicone resin, nano silicon dioxide, silane coupling agent and polysilazane resin; the size range of the nano silicon dioxide is 10nm.

[0121] The mass ratio of hydrogenated silicone oil: silicone resin: nano-silica: silane coupling agent: polysilazane resin is 2.5:15:1:0.6:5.

[0122] Embodiment D:

[0123] A method for preparing a stain-resistant, non-slip, and wear-resistant composite layer, comprising:

[0124] (1) Spray the anti-slip dry granular glaze on the brick with the base glaze attached. The construction parameters are: specific gravity 1.6g / cm 3 , glaze spraying amount 100g / m2, nozzle aperture 0.43mm; base glaze was purchased randomly on the market;

[0125] The anti-slip dry granule glaze, by mass percentage, includes: 80% antique protection glaze and 20% matte dry granules;

[0126] Antique protective glaze, including, by mass: 20 parts of potassium feldspar, 25 parts of sodium feldspar, 10 parts of kaolin, 8 parts of zinc oxide, 3 parts of burned talc, 15 parts of wollastonite, 25 parts of barium carbonate and 8 parts of strontium carbonate;

[0127] The chemical composition of the matte dry granules, by mass percentage, includes: SiO2 65%, Al2O3 6%, K2O 3%, CaO15%, MgO 1%, BaO 2% and ZnO 8%;

[0128] The antique protective glaze is ball-milled to a 325-mesh sieve residue of 0.2%; the particle range of the matte dry particles is 200-300 mesh, and the initial melting temperature is 1200℃.

[0129] (2) Spray the corundum slurry on the surface of the brick; the glazing parameters of the corundum slurry are: specific gravity 1.4g / cm 3 , glaze spraying amount 50g / m2, nozzle aperture 0.52mm;

[0130] The raw materials of the corundum slurry include, by mass percentage, 10% of corundum powder and 90% of suspending agent; the particle size of the corundum powder ranges from 500 to 1000 meshes. The suspending agent is purchased randomly on the market.

[0131] (3) The substrate is transferred to a kiln at 1200°C for firing; the bricks are taken out of the kiln and cooled to 100°C; a hydrophobic and stain-resistant coating is sprayed on the bricks, and the hydrophobic and stain-resistant coating is cured by the residual heat of the bricks themselves; and the bricks are left to stand for 8 hours.

[0132] The hydrophobic and anti-fouling coating comprises: hydrogenated silicone oil, silicone resin, nano silicon dioxide, silane coupling agent and polysilazane resin; the size range of the nano silicon dioxide is 50nm.

[0133] The mass ratio of hydrogenated silicone oil: silicone resin: nano-silica: silane coupling agent: polysilazane resin is 1:5:2:0.1:10.

[0134] The performance of Examples C and D was tested, and the results are shown in Table 3.

[0135] Table 3 - Performance Tests of Examples C and D

[0136] project Anti-slip Mohs hardness Example C R11 Level 8 Example D R11 Level 8

[0137] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A stain-resistant, non-slip, and wear-resistant composite layer, characterized in that: The bottom surface includes: a wear-resistant and anti-skid layer and a corundum layer; The wear-resistant and anti-skid layer is made of anti-skid dry granular glaze; the raw materials of the anti-skid dry granular glaze include, by mass percentage: 10-80% of antique protective glaze and 20-90% of matte dry granules; The antique protective glaze is ball-milled to a 325-mesh sieve residue of 0.2-1.5%, and the content of BaO plus MgO is greater than 20%; the particle size range of the matte dry particles is 120-300 mesh, and the initial melting temperature is greater than 1200°C; The corundum layer is made of corundum slurry; the raw materials of the corundum slurry include, by mass percentage: 10-60% corundum powder and 40-90% suspending agent; The particle size of the corundum powder ranges from 200 to 1200 meshes.

2. The anti-fouling, anti-skid and wear-resistant composite layer according to claim 1, characterized in that: Also includes: Hydrophobic and stain-resistant coating; The hydrophobic and anti-fouling coating is applied on the surface of the corundum layer; The hydrophobic and anti-fouling coating is made of a hydrophobic and anti-fouling paint, and the hydrophobic and anti-fouling paint comprises: hydrogenated silicone oil, organic silicone resin, nano silicon dioxide, a silane coupling agent and a polysilazane resin.

3. The anti-fouling, anti-skid and wear-resistant composite layer according to claim 1, characterized in that: The antique protective glaze comprises, by weight, 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 6 to 10 parts of kaolin, 2 to 8 parts of zinc oxide, 3 to 10 parts of calcined talc, 5 to 15 parts of wollastonite, 15 to 25 parts of barium carbonate and 2 to 8 parts of strontium carbonate.

4. The anti-fouling, anti-skid and wear-resistant composite layer according to any one of claims 1 to 3, characterized in that: Matt dry particles, by mass percentage, include: SiO2 45-65%, Al2O3 6-15%, K2O 3-10%, Na2O 0-2.5%, CaO6-15%, MgO 0-1%, BaO 0-2% and ZnO 3-12%.

5. A stain-resistant, non-slip and wear-resistant tile, characterized in that: include: A body and a stain-resistant, non-slip, and wear-resistant composite layer as claimed in any one of claims 1 to 4; The anti-fouling, anti-skid and wear-resistant composite layer is arranged on the surface of the blank.

6. A method for preparing a stain-resistant, non-slip, and wear-resistant composite layer, characterized in that: The method for preparing a dirt-resistant, non-slip and wear-resistant composite layer according to any one of claims 1 to 4 comprises the following steps: (1) applying anti-skid dry granular glaze cloth to the surface of the substrate to form a wear-resistant and anti-skid layer; (2) applying corundum slurry to the wear-resistant and anti-skid layer to form a corundum layer; (3) The substrate is transferred to a kiln and fired at 1200-1300°C.

7. The method for preparing a stain-resistant, non-slip and wear-resistant composite layer according to claim 6, characterized in that: In the step (1), the glazing parameters of the anti-slip dry granular glaze are: specific gravity 1.2-1.6 g / cm 3 , glaze spraying amount 100 ~ 250g / square meter, nozzle aperture 0.43 ~ 0.72mm; In the step (2), the glazing parameters of the corundum slurry are: specific gravity 1.05-1.4 g / cm 3 The glaze spraying amount is 50-200g / square meter, and the nozzle aperture is 0.36-0.52mm.

8. The method for preparing a stain-resistant, non-slip and wear-resistant composite layer according to claim 6, characterized in that: Also includes: step (4); Step (4): After the substrate is taken out of the kiln, it is cooled to 100-250° C., a hydrophobic and anti-fouling coating is applied to the surface of the substrate, and the hydrophobic and anti-fouling coating is cured by the residual heat of the substrate itself; The hydrophobic and anti-fouling coating includes: hydrogenated silicone oil, polysilazane resin, nano-silica and silane coupling agent.

9. The method for preparing a stain-resistant, non-slip and wear-resistant composite layer according to claim 8, characterized in that: In the step (4), the hydrophobic and anti-fouling coating is applied by spraying.

10. Use of a composite layer in preparing stain-resistant, non-slip and wear-resistant ceramic tiles, characterized in that: The composite layer is a stain-resistant, anti-skid, and wear-resistant composite layer as described in any one of claims 1 to 4, or is prepared by the method for preparing a stain-resistant, anti-skid, and wear-resistant composite layer as described in any one of claims 6 to 9.